The Evolution of Erythrocytes Becoming Red in Respect to Fluorescence - Hertz, Laura; Ruppenthal, Sandra; Simionato, Greta; Quint, Stephan; Kihm, Alexander; Abay, Asena; Petkova-Kirova, Polina; Boehm, Ulrich; Weissgerber, Petra; Wagner, Christian; Laschke, Matthias W.; Kaestner, Lars (Frontiers in Physiology, 2019)
Very young red blood cells, namely reticulocytes, can be quite easily recognised and labelled by cluster of differentiation antibodies (CD71, transferrin receptor) or by staining remnant RNA with thiazol orange. In contrast age specific erythrocyte labelling is more difficult in later periods of their life time. While erythrocytes contain with band 4.1 protein, a molecular clock, so far it has not been possible to read this clock on individual cells. One concept to track erythrocytes during their life time is to mark them when they are young, either directly in vivo or ex vivo followed by a transfusion. Several methods like biotinylation, use of isotopes or fluorescent labelling have proved to be useful experimental approaches but also have several inherent disadvantages. Genetic engineering of mice provides additional options to express fluorescent proteins in erythroytes. To allow co-staining with popular green fluorescent dyes like Fluo-4 or other fluorescein-based dyes, we bred a mouse line expressing a tandem red fluorescent protein (tdRFP). Within this Brief Research Report, we provide the initial characterisation of this mouse line and show application examples ranging from transfusion experiments and intravital microscopy to multicolour flow cytometry and confocal imaging. We provide a versatile new tool for erythrocyte research and discuss a range of experimental opportunities to study membrane processes and other aspects of erythrocyte development and aging with help of these animals.